Report on the Population Projections Worked Out Under the Guidance of the Expert Committee Set Up By The Planning Commission Under The Chairmanship of the Registrar General, India - Ministry of Home Affairs Government of India (Ministry of Home Affairs Government of India, 1986)
An Expert Committee on Population Projections under the Chairmanship of the Registrar General, India, was set up by the Planning Commission in 1958 to provide a set of projections of population of India and the States for use in the preparation of the Third Five Year Plan The projections were then made available to the Planning Commission up to 1971 pending the release of the 1961 Census results From that time onwards the Expert Committee has been re-activated from time to time to revise the projections on the strength of the latest available information from the Census.
Ministry of Home Affairs Government of India
Ministry of Home Affairs Government of India